Comparison of CVM Stages and Maxillary Canine Calcification Stages for Determination of Skeletal Maturity (Medical Forum Monthly, 2023)
Objective: To determine correlation between maturation of cervical vertebrae (CVM) stages and maxillary canine mineralization phases in determining the skeletal maturity.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Orthodontic Department, de'Montmorency College of dentistry, Lahore, from March 2021 to October 2022.Materials and Methods: The study was conceived at orthodontic centre of public sector institute where lateral cephalograms and OPG radiographs of orthodontic subjects were used using established selection criteria.Results: Descriptive statistics of CVM stages and Maxillary Canine calcification (DI) stages were calculated. Results of Spearman Coefficient of Correlation showed a very strong positive linear relationship between CVM stages and maxillary canine calcification stages.Conclusion: There was very strong positive linear relation between CVM phases and maxillary canine calcification stages.